Dvanaest osnovnih dimenzija visokokvalitetne indo-mediteranske dijete: TWELVE FUNTAMENTAL DIMENSIONS OF A HIGH QUALITY INDO-MEDITERRANEAN DIET - B Singh, Ram; Isaza , Adrian; Fatima, Ghizal; Maheshwari, Anuj; Verma, Narsingh; Joshi, Shanshank; Mishra, Richa; Tiwari, Poonam; Shilpa Joshi; Yeluri, Sudha R; Aminat Magamedova; Magamedov, Magomed (Scripta Medica, 2023)
High-quality Indo-Mediterranean foods are characterised with unrefined, unprocessed foods, whole grains such as dry millets and beans and porridge. Vegetables such as leaves and gourds, nuts, and fruits such as apples, grapes, papaya, guava, etc are major components of this diet. It seems that healthy vegetable oils such as olive, mustard, rape seed oil and protein sources that are beneficial; beans, pulses, cottage cheese are crucial in this diet. Among animal sources, white meats; such as sea foods should also be part of this diet. Vegetables and spices with medicinal properties; gourds, turmeric, fenugreek, coriander and cumin may also be called high quality nutraceutical foods, respectively. There is a need to find out traditional foods from all other countries which may be protective and healthy. There is evidence that calories have tremendous role in weight gain and weight loss. It seems that emphasis on food quality is crucial for prevention of oxidative stress and inflammation in the adipocytes, which predispose obesity and risk of cardiovascular diseases (CVDs) and diabetes. There are gaps in knowledge about the qualities of traditional foods, which prompt authors to present this communication.